Mitigation measures of peak hour traffic congestion - Sia Wei Kai (2015)
This report focus on a study of the mitigation measures on peak hour traffic congestion. Through detail understanding of the impact of congestion, and the problems that congestions leads on to. The three methods to meet the peak hour traffic congestion is explained using the supplying of existing measures, reducing the demands of commuters and the different traffic improvement schemes. A general study is done and the problems of public transportation are identified with solution explain for Singapore. A comparison study is done with neighbouring Asian countries and their differences and similarity are highlighted. A survey is conducted to question the commuters on their take on Peak Hour traffic congestion. Survey is also designed to understand the public views on congestion and their behaviour mood during congestion to understand the effectiveness of existing measures to private commuters. A study is done to check if a new alternative of transport is viable with the objective of creating service integration of different transportation modes through a new way of transition. Result of different surveys are compiled, analysed and concluded. There had been a rise in a shift from private transport owners to become public transport commuters. However, this creates a high demand for public transport which is required to be managed. Additional public transportation has been provided and existing transportation systems improved. Alternative new route of transport are created, but result from survey shows that commuters would still prefer to take the fastest route to their destination. Thus, with public transport reaching its saturation, there have to be a new available mode of transport to solve the transportation problem. Through the introduction of Bicycle as a public transport, it would provide a new alternative mode of transport with ideally equivalent time and cost spent on transportation. This would serve a replacement transition service for commuters to travel to their destination according to their individual needs and enhance serve integrations of all the transportation systems in Singapore. It creates a balance between a time saving and cost saving route.